Histochemistry, chemical composition and antioxidant activity of Citrus aurantium L. essential oil during leaf development. Issue 4 (4th July 2022) - Mejri, Houda; Khetatfa, Takoua; Aidi Wannes, Wissem; Smaoui, Abderrazak; Saidani Tounsi, Moufida
ABSTRACT: Essential toils are important natural products of aromatic plants, which are mostly biosynthesized and accumulated in secretory cavities. In this study, the impact of leaf developmental stages was investigated on secretory structure, chemical composition and antioxidant activity of Citrus aurantium essential oil. The secretory cavity of young leaf had more essential oil droplets than that of mature leaf which indicated that the young leaf constitutes a mass production of essential oil in Citrus aurantium leaf. In fact, the young leaves exhibited the highest essential oil yield (0.77%), followed by intermediate (0.50%) and mature (0.25%) leaves. The major constituent of the leaf essential oil composition was sabinene (33.17–44.83%), followed by E -β-ocimene (7.57–8.21%) in young and intermediate leaves but by δ-3-Carene (12.81%) in mature leaves. The antioxidant activities of Citrus aurantium essential oil at different leaf stages were evaluated by using DPPH radical scavenging, reducing power and β-carotene-linoleic acid bleaching assays. Independently of leaf development, Citrus aurantium essential oil showed a strong capacity to reduce iron while it had a low ability to scavenge DPPH radicals and to bleach β-carotene.